Characteristics of second primary breast cancer after ovarian cancer: a Korea central cancer registry retrospective study - Lee, Eun-Gyeong; Lim, Jiwon; Ha, Hyeong In; Lim, Myong Cheol; Chang, Yoon Jung; Won, Young-Joo; Jung, So-Youn (Frontiers in Oncology, 2023)
Background: Second primary cancer has become an important issue among cancer survivors. This study sought to determine the differences in clinicopathologic outcomes between second primary breast cancer (SPBC) after ovarian cancer and primary breast cancer (PBC) in the Republic of Korea.2 Methods and Materials: We searched the Korea Central Cancer Registry and identified 251,244 breast cancer cases that were diagnosed between 1999 and 2017. The incident rate and standardized incidence ratio (SIR) were calculated. Demographic and clinical characteristics and overall survival (OS) rates were estimated according to age, histological type, and cancer stage.Results: Among the 228,329 patients included, 228,148 were patients with PBC, and 181 patients had SPBC diagnosed after ovarian cancer (OC). The mean ages at diagnosis were 56.09 ± 10.81 years for SPBC and 50.65 ± 11.40 years for PBC. Patients with SPBC were significantly less likely than patients with PBC to receive adjuvant radiotherapy (14.92% vs. 21.92%, p = 0.02) or adjuvant chemotherapy (44.75% vs. 55.69%, p < 0.01). Based on the age-standardized rate (ASR), the incidence of SPBC after OC was 293.58 per 100,000 ovarian cancer patients and the incidence of PBC was 39.13 per 100,000 women. The SIR for SPBC was 1.27 (1.09-1.46, 95% Confidence interval) in the patients overall. The 5-year OS rates were 72.88% and 89.37% for SPBC and PBC (p < 0.01). The OS rate in SPBC decreased significantly with advanced stage and older age.The incidence of breast cancer is about 1.27 times higher in ovarian cancer patients than in healthy people. The survival outcomes were worse for SPBC than for PBC and were related to older age and advanced stage. Active screening for breast cancer is necessary in ovarian cancer patients.